Analysis of travel-time to HIV treatment in sub-Saharan Africa reveals inequities in access to antiretrovirals - Justin T. Okano; Andrea Low; Luckson Dullie; Wongani Mzumara; Harriet Nuwagaba-Biribonwoha; Sally Blower (Communications Medicine)
Abstract Background UNAIDS proposes ending inequalities in access to HIV treatment. We use data from nationally-representative Population-Based HIV Impact Assessment (PHIA) surveys for Eswatini, Malawi, and Zambia to identify inequities in one-way travel-time to access antiretroviral therapy (ART) for people with HIV (PWH). Methods Using biometric data from the PHIAs, we construct Epidemic Surface Prevalence maps and estimate treatment coverage. Self-reported travel-time data were fit using logistic cumulative distribution functions. Multivariable logistic regression models were used to examine relationships between travel-time, urban-rural residency, age, and sex. Results We find the majority of PWH on ART are women: Eswatini (69.4%), Malawi (64.8%), Zambia (63.0%). The majority on ART reside in rural areas in Malawi (74.6%) and Eswatini (71.0%), but in urban areas in Zambia (61.9%). Travel-time distribution functions show, on average, PWH in Eswatini have the shortest travel-times; travel-times in Malawi are slightly longer than in Zambia. 56.4% (Malawi), 50.5% (Zambia), and 37.4% (Eswatini) of treated individuals could not access ART within one hour; many travel more than two hours: 20.6% (Zambia), 19.0% (Malawi), 10.5% (Eswatini). In all countries, the odds of traveling one or more hours are significantly higher in rural than urban areas. In Eswatini and Zambia, women have significantly higher odds than men of traveling one or more hours. Conclusions Many PWH spend considerable time traveling to access ART. Substantial inequities exist, disadvantaging rural populations in all three countries, and women in Eswatini and Zambia. Achieving UNAIDS’ goal will require identifying drivers of inequities and designing strategies to minimize them.